METHODOLOGY OF COGNITIVE-DISCURSIVE MODELLING OF LITERARY TRANSLATION (case study of Ukrainian retranslations of W. Shakespeare’s tragedies of the 19th–21st centuries) - Yana V. Boiko (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2024)
The article provides theoretical and methodological substantiation for the step-by-step construction of a cognitive-discursive model of the diachronic plurality in translation of a time-remote original work, which appears as a tool for revealing the internal mechanisms of translating a literary work and determining the criteria for the adequacy of the original and translation. This is a case study of W. Shakespeare’s tragedies as time-remote original works of England of the late 16th – early 17th centuries and their Ukrainian retranslations of the 19th–21st centuries. The algorithm of the complex methodology of cognitive-discursive modelling of literary translation, which incorporates the methods of discourse analysis and cognitive translation studies, involves five stages of construction of three modules: discursive, cognitive, and retranslation. The construction of a discursive module, the aim of which is to reveal the objective and subjective factors that influence the process and result of the translator’s interpretation of a time-remote original work, involves the construction of three components – extralingual, lingual, and interpretation, which takes place in the first three stages. The fourth stage is the building of a cognitive module, which reveals the internal mechanisms of the translation process caused by cognitive consonance (harmonious identity of the mental processes of the author and the translator) or cognitive dissonance (epistemological, ideological, and cultural-aesthetic). Cognitive consonance and cognitive dissonance result from the similarities and differences in the contexts of original creation and retranslations, which are previously defined in the discursive module. The translator’s decision to choose one or another translation strategy and local tactic in conditions of cognitive consonance or cognitive dissonance determines different degrees of cognitive proximity of the original and the translation: cognitive equivalence, cognitive analogy, and cognitive variance. The fifth stage is the construction of a retranslation module, which affirms that the translator’s choice of strategy (modernization or archaization, domestication or foreignization) and tactic (reproductive or adaptive) of transformational translation is conditioned by cognitive consonance or dissonance. The relevance of the research is determined by its appeal to the leading cognitive-discursive paradigm of modern translation studies and by the tendency of cognitive translation studies for the translation process modelling, according to which not only the translation result is the subject of study, but also the prerequisites that determine the translator’s approach to the reproduction of the original text in one way or another. Analysis and comparison of retranslations of a time-remote original text in the course of modelling the process of literary translation allows following the influence of discursive and cognitive factors on the process and result of translation. The creation of the cognitive-discursive model of the diachronic plurality in translation of the time-remote original text explains the translation decisions regarding the choice of the general strategy and local tactic of retranslations and, respectively, the diachronic plurality in translations of a time-remote original text.